Correlates of work productivity and maternal competence after having a baby: the roles of mother-infant bonding and maternal subjective experiences - Pia Tohme; Rudy Abi-Habib (BMC, 2022)
Abstract Background The law in Lebanon allows new mothers to take up to 10 weeks paid maternity leave, and some private organizations choose to give fathers 2 days of paternity leave in the absence of clear legislation. This falls short of the 6 months recommended for mothers in the literature. Methods The sample consisted of 97 Lebanese mothers with children between 6 and 24 months of age. First, we examined correlations between the length of maternity leave and measures of work productivity and maternal sense of competence in their new role as a parent. Second, we explored correlations between the length of maternity leave and mother-child adjustment measures (mother-infant bonding, maternal stress, and parenting guilt). Finally, we looked for predictors of work productivity and maternal sense of competence in demographic variables, mother-child adjustment measures, and partner attachment scores. Results Results showed significant correlations between work productivity and maternal sense of competence, irrespective of the length of maternity leave. Regression analyses showed that working for pleasure, mother-infant healthy bonding, and positive subjective experience of being back to work were significant predictors of work productivity, and that maternal stress predicted maternal competence. Conclusion These findings are discussed within the framework of providing suggestions facilitating mothers' transition back to work and increasing work productivity after having a baby.